Straight-sided beer and cider glasses to reduce alcohol sales for on-site consumption: A randomised crossover trial in bars. - Brocklebank, LA; Blackwell, AKM; Marteau, TM; Hollands, GJ; Fletcher, PC; De-Loyde, K; Morris, RW; Pilling, MA; Pechey, R; Maynard, OM; Attwood, AS; Munafò, MR (Elsevier, 2021)
Background Straight-sided glasses can slow the rate of lager consumption in a laboratory setting compared with curved glasses. Slower drinking rates may lower overall alcohol consumption. Glass shape is therefore a potential target for intervention. The aim of this randomised crossover trial was to estimate the impact of serving draught beer and cider in straight-sided glasses, compared with usual, predominantly curved glasses, on alcohol sales for on-site consumption in bars.